THE MANAGEMENT OF LABOR TRAINING IN THE SCIENTIFIC ACTIVITY FOR SOCIAL DEVELOPMENT - Alberto Leyva Figueredo; Laura Leticia Mendoza Tauler; Orlando Martínez Cuba (University of Las Tunas, 2018)
It presents an experience that distinguishes the management of labor training in scientific activity, as a university development project, based on an integrative conception that guides professionals towards the provision of a service and / or the obtaining of products of utility and necessity Social transformation in the course of life. It makes it possible to develop the personality qualities of the work, which together allow directionality to the professional's performance to be involved in the solution of the problems present in the socio-labor context. There are also practical requirements that take into account cultural traditions, from the process of socialization of systematized codes of culture, typical of school-university-business relations and socio-cultural codes coming from the environment through the affective areas , Socio-moral development, intellectual, cognitive and aesthetic taste. It has a practice accumulated in research for more than 20 years, in undergraduate and postgraduate training where the research results are part of the project associated with the National Program of the Center for Studies for Labor Training. The impacts have a national and provincial scope, are endorsed by the scientific community since its presentation in numerous events, methodological activities, socialization workshops, student scientific work, courses, diplomas, diplomas, postgraduate specialty in Management and Development of Training Laboral, master's thesis, doctorate; As well as publications in indexed journals and the obtaining of different prizes.